2017
DOI: 10.3390/ma10101200
|View full text |Cite
|
Sign up to set email alerts
|

L21 and XA Ordering Competition in Hafnium-Based Full-Heusler Alloys Hf2VZ (Z = Al, Ga, In, Tl, Si, Ge, Sn, Pb)

Abstract: For theoretical designing of full-Heusler based spintroinc materials, people have long believed in the so-called Site Preference Rule (SPR). Very recently, according to the SPR, there are several studies on XA-type Hafnium-based Heusler alloys X2YZ, i.e., Hf2VAl, Hf2CoZ (Z = Ga, In) and Hf2CrZ (Z = Al, Ga, In). In this work, a series of Hf2-based Heusler alloys, Hf2VZ (Z = Al, Ga, In, Tl, Si, Ge, Sn, Pb), were selected as targets to study the site preferences of their atoms by first-principle calculations. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Thus, the PBE functional should be suitable for the further studies on the electronic and magnetic properties of the MG/CMS bilayers. It can also be seen that the Mn I and Mn II have opposite magnetic moment for D0 3 - and D0 22 -MG bulks, and moreover, D0 3 -MG bulk is fully compensated ferrimagnet due to the spin magnetic moments of Mn I atoms align antiparallelly to those of the Mn II atoms and the total magnet is equal to zero 44 , while D 0 22 -MG bulk is partially compensated ferrimagnet due to the antiparallel spin magnetic moments of Mn I and Mn II atoms and its low saturation magnetization. The L1 0 -MG and L2 1 -CMS bulks are ferromagnets due to the atomic moments of Mn or Co are parallel to each other and they have nonzero net magnetization.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, the PBE functional should be suitable for the further studies on the electronic and magnetic properties of the MG/CMS bilayers. It can also be seen that the Mn I and Mn II have opposite magnetic moment for D0 3 - and D0 22 -MG bulks, and moreover, D0 3 -MG bulk is fully compensated ferrimagnet due to the spin magnetic moments of Mn I atoms align antiparallelly to those of the Mn II atoms and the total magnet is equal to zero 44 , while D 0 22 -MG bulk is partially compensated ferrimagnet due to the antiparallel spin magnetic moments of Mn I and Mn II atoms and its low saturation magnetization. The L1 0 -MG and L2 1 -CMS bulks are ferromagnets due to the atomic moments of Mn or Co are parallel to each other and they have nonzero net magnetization.…”
Section: Resultsmentioning
confidence: 91%
“…We examined the formation and cohesive energies of YRhTiGe compound to show the structural stability of this EQH compound. The formation and cohesive energies can be obtained by the following formulae [ 42 , 43 , 44 , 45 ]: where is the YRhTiGe’s total energy for per formula unit, and , , , and are the total energies per atom for each Y, Rh, Ti, and Ge atom in the bulk form, respectively. , , , and are the individual energies of the Y, Rh, Ti, and Ge, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The above parameters ensure the accuracy of the calculated results based on the references [39]. Similar methods to investigate the electronic structures of Heusler alloys can be found in [30][31][32][33].…”
Section: Calculation Methodsmentioning
confidence: 76%
“…For example, Kogachi et al [29] studied the electronic and magnetic properties of Co 2 MnZ (Z = Si, Ge, Sn). Liu et al [30] investigated the electronic structures of Mn 2 CoZ (Z = Al, Si, Ge, Sn, Sb) in detail and found two mechanisms to induce the band gap for minority spin states near the Fermi level; Wang et al [31] studied the electronic and magnetic properties of FH alloy Zr 2 CoZ (Z = Al, Ga, In, Si, Ge, Sn, Pb, Sb) and found that the half-metallicities are robust against lattice distortion; Wang et al also studied the site preferences of the Titanium-based [32] and Hf 2 V-based [33] FH alloys, and found that most of these alloys are likely to form the L2 1 structure instead of the XA structure. Thus, the traditional site-preference rule (SPR) may not be suitable for all FH alloys, such as X 2 YZ, where X is a low-valent transition metal element, such as, Ti, Zr, Sc, and Hf.…”
Section: Introductionmentioning
confidence: 99%